The life of Saint Patrick - Reynolds, Quentin James 1902-1965.; Gorsline, Douglas W. 1913-. (New York Random House, 1955)
A biography of the British boy, captured by raiding Irish warriors at age sixteen, who performed miracles, ended the power of the Druid priests over the Irish people, and converted the Irish kings and their people to Christianity.
Keywords: Patrick -- Saint -- 373n-463n -- Juvenile literature; Patrick -- Saint -- 373n-463n.; Christian saints -- Juvenile literature. -- Ireland -- Biography; Ireland -- Church history -- Juvenile literature. -- To 1172.